Influence of Employee Competence and Work Environment on The Quality of Fire Management Services With AHP Method - Dewi Laraswati; Marlina Marlina; Indarti Indarti (Universitas Islam Kuantan Singingi, 2021)
The purpose of this study is to find out the influence of employee competence and the work environment on the quality of fire management services in the South Jakarta Administrative City Fire and Rescue Service Tribe. The method used is a quantitative method through the dissemination of questionnaires, with a population of 473 people or respondents and the sample is 83 people using SPSS Version 23 for windows with the aim to facilitate and ensure the calculation and processing of data has been done correctly.